Opportunities and Challenges for Islamic Education in Society 5.0 - Irfan Setia Permana W; Naomi Ainun Hasanah (Islam Transformatif : Journal of Islamic Studies, 2024)
This study thoroughly investigates the opportunities and challenges encountered by Islamic education in adapting to the dynamics of Society 5.0. Employing a qualitative approach supported by an extensive literature review, the research synthesizes diverse scholarly perspectives to elucidate the transformative potential of digital technologies within Islamic educational frameworks. The findings highlight significant opportunities, including the enhancement of educators’ digital competencies, the development of innovative pedagogical models, and the strategic integration of advanced technologies to foster more effective and accessible educational practices. These advancements signify a promising pathway for strengthening the role of Islamic education in contemporary society. However, the research also highlights critical challenges, particularly the necessity for educators to navigate rapidly evolving technological landscapes while upholding the core Islamic values integral to educational principles. Through a comparative framework, the study draws lessons from countries with advanced digital integration, identifying best practices that can inform the evolution of Islamic education. The findings suggest that sustaining the relevance and vitality of Islamic education in Society 5.0 necessitates a deliberate approach to technology adoption, supported by adaptive policy frameworks and continuous professional development. These measures are pivotal in ensuring institutional resilience and advancing Islamic education amidst the complexities of the digital era.